Social Jetlag and Cardiometabolic Risk in Preadolescent Children - Castro, Nicholas; Diana, Jake; Blackwell, Jade; Faulkner, James; Lark, Sally; Skidmore, Paula; Hamlin, Michael; Signal, Leigh; Williams, Michelle A.; Stoner, Lee (Frontiers in Cardiovascular Medicine, 2021)
Objective: Childhood cardiometabolic disease risk (CMD) has been associated with short sleep duration. Its relationship with other aspects of sleep should also be considered, including social jetlag (SJL) which represents the difference between a person's social rhythms and circadian clock. This study investigated whether childhood CMD risk is associated with sleep duration, sleep disturbances, and SJL. Study Design: The observational study included 332 children aged 8–10 years (48.5% female). The three independent variables were sleep duration, sleep disturbances, and SJL. SJL was calculated as the variation in hours between the midpoint of sleep during free (weekend) days and work/school days. Eleven cardiometabolic biomarkers were measured, including central blood pressure, lipids, glycated hemoglobin, arterial wave reflection, and glucose. Underlying CMD risk factors were identified using factor analysis. Results: Four underlying CMD risk factors were identified using factor analysis: blood pressure, cholesterol, vascular health, and carbohydrate metabolism. Neither sleep disturbances nor sleep duration were significantly associated with any of the four CMD factors following adjustments to potential confounders. However, SJL was significantly linked to vascular health (p = 0.027) and cholesterol (p = 0.025). Conclusion: These findings suggest that SJL may be a significant and measurable public health target for offsetting negative CMD trajectories in children. Further studies are required to determine biological plausibility.